2001
DOI: 10.1161/hc4101.097248
|View full text |Cite
|
Sign up to set email alerts
|

Differential Characteristics of Neural Circulatory Control

Abstract: Background-Reappearance of low-frequency (LF) (Ϯ0.10 Hz) oscillations in RR interval (RR) after cardiac transplantation is indicative of sympathetic efferent reinnervation. We hypothesized that restored LF oscillations in RR in heart transplant recipients (HTRs) are linked to oscillations in muscle sympathetic nerve traffic (MSNA). Methods and Results-RR, RR variability, and MSNA were recorded 5Ϯ2 months (nϭ7, short-term HTRs) and 138Ϯ8 months (nϭ7, long-term HTRs) after heart transplantation and compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
25
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 38 publications
6
25
0
Order By: Relevance
“…These studies revealed that cyclosporine and time from heart transplantation contribute to MSNA increase in HTRs. 2,3 Our study confirms previous observations of increased MSNA in long-term HTRs. It provides a new insight into sympathetic regulation after heart transplantation.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These studies revealed that cyclosporine and time from heart transplantation contribute to MSNA increase in HTRs. 2,3 Our study confirms previous observations of increased MSNA in long-term HTRs. It provides a new insight into sympathetic regulation after heart transplantation.…”
Section: Discussionsupporting
confidence: 91%
“…Heart transplantation initially decreases the MSNA related to the heart failure state, because it returns to normal values within 1 year after the surgical procedure, 16 although this normalization does not seem to be permanent. 2,3 Only a few studies have used direct recording of nerve traffic to unravel sympathetic activation after heart transplantation. These studies revealed that cyclosporine and time from heart transplantation contribute to MSNA increase in HTRs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Afferent reinnervation is supported by reports of angina accompanied by objective evidence of cardiac ischemia. 9,10 Evidence for sympathetic reinnervation derives from the emergence of a low-frequency heart rate (HR) variability in some transplants, [11][12][13] and the appearance of appropriate, albeit diminished, reflex changes in HR. 11,[14][15][16] In addition, experiments suggest catecholamine uptake, storage or release from presumed cardiac sympathetic postganglionic neurons in the transplanted heart.…”
mentioning
confidence: 99%